The potassic sedimentary rocks in Gale Crater, Mars, as seen by ChemCam on board Curiosity. Issue 5 (13th May 2016) - Le Deit, L.; Mangold, N.; Forni, O.; Cousin, A.; Lasue, J.; Schröder, S.; Wiens, R. C.; Sumner, D.; Fabre, C.; Stack, K. M.; Anderson, R. B.; Blaney, D.; et al.
Abstract: The Mars Science Laboratory rover Curiosity encountered potassium‐rich clastic sedimentary rocks at two sites in Gale Crater, the waypoints Cooperstown and Kimberley. These rocks include several distinct meters thick sedimentary outcrops ranging from fine sandstone to conglomerate, interpreted to record an ancient fluvial or fluvio‐deltaic depositional system. From ChemCam Laser‐Induced Breakdown Spectroscopy (LIBS) chemical analyses, this suite of sedimentary rocks has an overall mean K2 O abundance that is more than 5 times higher than that of the average Martian crust. The combined analysis of ChemCam data with stratigraphic and geographic locations reveals that the mean K2 O abundance increases upward through the stratigraphic section. Chemical analyses across each unit can be represented as mixtures of several distinct chemical components, i.e., mineral phases, including K‐bearing minerals, mafic silicates, Fe‐oxides, and Fe‐hydroxide/oxyhydroxides. Possible K‐bearing minerals include alkali feldspar (including anorthoclase and sanidine) and K‐bearing phyllosilicate such as illite. Mixtures of different source rocks, including a potassium‐rich rock located on the rim and walls of Gale Crater, are the likely origin of observed chemical variations within each unit. Physical sorting may have also played a role in the enrichment in K in the Kimberley formation. The occurrence of these potassic sedimentary rocks provides additional evidence for the chemical diversity of the crust exposed at Gale Crater. Key Points: Mean K2 O abundance in sedimentary rocks >5 times higher than that of the average Martian crust Presence of alkali feldspars and K‐phyllosilicates in basaltic sedimentary rocks along the traverse The K‐bearing minerals likely have a detrital origin